Cem Mecmuası'nın incelenmesi (1910-1912) - Ergün, Ebubekir (My University, 2009)
II. Meşrutiyet dönemi Türk basın hayatında önemli bir dönüm noktasıdır. Süreli yayınlarda sayı ve tür bakımından önemli bir artış görülür. Bu artış en fazla mizah basınında görülür. Tanzimat’tan beri mizah siyaseti ve kamuoyunu etkilemenin en çok başvurulan yolu olmuştur. II. Meşrutiyet döneminde mizah basını hem yapısal hem tematik bakımdan önemli ve köklü bir değişim geçirir. Türk mizahının gerek karikatürde gerek mizah yazılarında geleneksel çizgiden modern çizgiye yöneldiği görülür. Bu değişimde en önemli rolü Cemil Cem’in ilk karikatürlerini yayımladığı Kalem, sonra Cemil Cem’in çıkardığı Cem dergisi oynar. Cem dergisi mizah basınına resim tarzı karikatür anlayışı yerine, çizgideki mizahı öne çıkaran modern bir anlayışı ve ilk portre karikatürü tarzını getirir. Bu bakımdan kendi döneminde ve kendisinden sonraki dönemin mizah basınını etkiler. Bunun dışında Cem dergisinin tarafsız bir yayın çizgisi takip etmesi dönemi için onu önemli kılan bir başka özelliktir. Bu çalışmada önce Tanzimat’tan II. Meşrutiyete kadar Türk mizah basını ve mizah anlayışı tarihsel süreci içinde değerlendirilmiştir. Cem dergisindeki mizah yazıları, içerik özelliklerine ve edebi türlerine göre tasnif edilerek incelenmiştir. Dergideki karikatürler, tematik dağılımına göre tasnif edilerek incelenmiş ve karikatürlerin tematik indeksleri çıkarılmıştır. Bu tezde, Cem dergisi hem yazılarındaki mizah anlayışı bakımından, hem de karikatürlere yansıyan mizah anlayışı bakımından incelenerek derginin mizah anlayışı ve Türk mizah basınındaki yenilikçi rolü tespit edilmeye çalışılmıştır. Tanzimat, II. Meşrutiyet, Mizah, Karikatür, Cemil Cem, mizah basını, Cem Dergisi

Second Constitutional Monarchy era is considered as one of the crucial milestones in Turkish Press history. The number of periodical publications increased during this era, mostly for the humor press. Humor is known as the most applied way to make an impact on public and politics since the 1839-76 reforms, which known as Tanzimat in Ottoman Empire History. Humor press went through in structural and thematic changes in terms of both theme and structure during the “Second Constitutional Monarchy era”. Turkish press turned towards modern line from the conservative one in caricature and humor articles during this age. Kalem publication played a huge role in this shift of direction where Cemil Cem published his first cartoons and Cem publication again where Cemil Cem published himself. Cem publication brought a new understanding and style with its modern approach that puts humor upfront in drawings rather than picture caricature approach and also became the first to use the portrait caricature style. Hence it made a big impact on the humor press that time and after. It’s impartial publication policy of Cem publication was another feature of it for the others to follow this magazine. With this research, Humor press and Humor understanding is evaluated within its historic process between Tanzimat and Second Constitutional Monarchy era. Humor articles in Cem magazine is analyzed in accordance with their content characteristics and literary genre, Caricatures in this magazine are examined according to their thematic range and thematic index is prepared. In this thesis, humor understanding of Cem magazine and its innovative role in Turkish humor press is examined by analyzing its approach in humor articles and caricatures. Tanzimat, II. Meşrutiyet, Second Constitutional Monarchy era, Humor, Caricature, Cemil Cem, Humor Press, Cem magazine, Cem Dergisi
Keywords: Basın; Gazeteler; Türk Dili